Reliability and factorial validity of non-specific and tennis-specific pre-planned agility tests; preliminary analysis - Sekulic, D.; Uljevic, O.; Peric, M.; Spasic, M.; Kondric, M. (Journal of Human Kinetics, 2017)
Agility is an important quality in tennis, yet there is an evident lack of studies focussing on the applicability of tennis-specific agility performances and comparing them to equivalent non-specific agility performances. The aim of this study was to evaluate the reliability and factorial validity of three tests of pre-planned agility, performed in specific (with a tennis racquet) and non-specific (without a tennis racquet) conditions. The sample consisted of 33 tennis players (13 males and 20 females; age: 18.3 ± 1.1 years and 18.6 ± 1.3 years; body height: 185.4 ± 51 cm and 169.3 ± 4.2 cm, 74.0 ± 4.4 kg and 61.2 ± 3.1 kg, respectively). The variables comprised three agility tests: a 20-yard test, a T-test and the Illinois test, all performed in both specific and non-specific conditions. Between-subject and within-subject reliability were found to be high (Cronbach Alpha: 0.93 to 0.98; Coefficient of Variation: 3 to 8%), with better within-subject reliability and stability of the measurement for specific tests. Pearson`s product moment correlations between the non-specific and specific agility performances were high (r =0.84), while factor analysis extracted only one significant latent dimension on the basis of the Guttman-Kaiser criterion. The results of the 20-yard test were better when the test was conducted in the specific conditions (t-test = 2.66; p < 0.05). For the Illinois test, superior results were recorded in the non-specific conditions (t-test = 2.96; p < 0.05), which can be explained by the test duration (about 20 s) and non-specific locomotion forms such as rotational movements. Considering the findings of the present study, when testing tennis-specific pre-planned agility, we suggest using tests of short duration (less than 10 s) and sport-specific types of locomotion.